PENGARUH KUALITAS PRODUK, DESAIN KEMASAN, PERSEPSI HARGA, CITRA MEREK TERHADAP LEMINERALE - Erza Ramadhan, Demas; Kussudyarsana (Universitas Putera Batam, 2024)
This study aims to investigate the factors that influence consumer repurchase intentions on the Le Minerale mineral water brand in Greater Solo. In response to the significant growth of the food and beverage industry, drinking water companies are vying to expand their market share, creating intense competition. The main focus of companies, including Le Minerale, is to maximize marketing strategies through product quality, competitive pricing, attractive packaging design, and building a positive brand image. This research focuses on students of Universitas Muhammadiyah Surakarta as the study population, identifies repurchase intention as the dependent variable, and analyzes independent factors such as product quality, packaging design, price perception, and brand image. This study contributes by expanding the understanding of repurchase intention among university students, taking these factors into account to guide water companies in developing more effective marketing strategies. By involving these new variables, this research is expected to provide valuable insights for marketing practitioners and management science.